2013
DOI: 10.1007/s10103-013-1427-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy on metalloproteinase MMP-2 and MMP-9 production and percentage of collagen types I and III in a papain cartilage injury model

Abstract: Osteoarthritis (OA) resulting from injury or disease is associated with increased levels of several matrix metalloproteinases (MMPs), which degrade all components of the complex extracellular matrix in the cartilage. The objective of this study is to investigate the effect of low-level laser therapy (LLLT) on papain-induced joint damage in rats by histopathology and analysis of metalloproteinase 2 and 9 production. Sixty male Wistar rats were randomly distributed into four groups of 15 animals: (1) non-injury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 29 publications
4
28
0
7
Order By: Relevance
“…These data are consistent with the literature, which shows that articular cartilage has networks of disorganized collagen and lower quantities in the advanced stage of OA. 45,46 In OA pathophysiology, the presence of type III collagen accelerates the degradation of type II collagen. 47 Several studies, clinical and experimental, have shown the effects of laser photobiostimulation in increased cell proliferation and repair cartilage tissue.…”
Section: Discussionmentioning
confidence: 99%
“…These data are consistent with the literature, which shows that articular cartilage has networks of disorganized collagen and lower quantities in the advanced stage of OA. 45,46 In OA pathophysiology, the presence of type III collagen accelerates the degradation of type II collagen. 47 Several studies, clinical and experimental, have shown the effects of laser photobiostimulation in increased cell proliferation and repair cartilage tissue.…”
Section: Discussionmentioning
confidence: 99%
“…O estudo de Alves et al (2013a) realizou análise histopatológica da articulação do joelho de ratos, a fim de observar os efeitos do tratamento com LBP, em diferentes tempos após a indução de OA com papaína. Sete dias após a indução de OA com papaína, observouse a presença de um processo inflamatório intrínseco, o qual foi substituído gradualmente por sinais de cronicidade.…”
Section: Discussionunclassified
“…Diversos métodos têm sido desenvolvidos e testados para induzir a OA de maneira artificial em animais (CHO et al, 2004), como coelhos, cães, equinos, ovelhas, camundongos e ratos (ALVES et al, 2013a;ALVES et al, 2013b;BAI et al, 2002;BROWN et al, 1998;CLEMMONS et al, 2002;DOS SANTOS et al, 2014;PALLOTTA et al, 2012). Dentre os métodos utilizados para indução de OA podemos citar a injeção de papaína (ALVES et al, 2013a;ALVES et al, 2013b;BROWN et al, 1998;DA ROSA et al, 2012;DOS SANTOS et al, 2014;TANAKA et al, 1992;), fluoresceína (OEGEMA e al., 1997), colagenase (KIKUCHI et al, 1998;VAN DEN BERG, 2001) e outros (BAI et al, 2002;HASHIMOTO et al, 2002;PALLOTTA et al, 2012;RATKAY et al, 1994;).…”
Section: Modelo Experimental De Indução De Oa Por Meio De Papaínaunclassified
See 2 more Smart Citations